Immunotherapy-Associated Hypothyroidism: Comparison of the Pre-Existing With De-Novo Hypothyroidism - Kristan, Megan M.; Toro-Tobon, David; Francis, Nnenia; Desale, Sameer; Bikas, Athanasios; Jonklaas, Jacqueline; Goyal, Rachna M. (Frontiers in Endocrinology, 2022)
Background: Immunotherapy has revolutionized the treatment of solid malignancies, but is associated with endocrine-related adverse events. Currently, information on thyroid toxicities is limited. This study aims to dissect the natural course of immunotherapy-induced hypothyroidism and provide guidance regarding diagnosis and management in patients with and without pre-existing hypothyroidism. Methods: A retrospective analysis was conducted using patients who received immunotherapy between 2010‐2019 within a multicenter hospital system. Participants were separated in three groups—those with pre-existing hypothyroidism, those who developed primary hypothyroidism and those with hypophysitis within a year of their first immunotherapy. Serial effects of immunotherapy on thyroid function tests (TFTs) and levothyroxine dosing were evaluated. Results: 822 patients were screened, with 85 determined to have pre-existing hypothyroidism, 48 de-novo primary hypothyroidism and 12 de-novo hypophysitis. All groups displayed fluctuations in TFTs around weeks 6‐8 of treatment. In the pre-existing hypothyroidism group, levothyroxine dose remained stable throughout 54 weeks. The observed mean levothyroxine dose was significantly lower than the mean calculated weight-based dose for all groups. This finding was most clinically significant for the de-novo hypophysitis group (mean difference: -58.3 mcg, p<0.0001). The mean 0.9 mcg/kg levothyroxine dose at week 54 for the de-novo hypophysitis group was statistically lower than the other groups (p=0.009). Conclusion: It is reasonable to screen with TFTs every 4 weeks, and space out TFTs surveillance to every 12 weeks after week 20. Our findings suggest a more conservative approach for levothyroxine dosing in those developing de-novo hypothyroidism, especially hypophysitis, such as initiating at 0.9-1.2 mcg/kg.